Enhancing Food Safety Standards in Kuah Kuwi Noodle MSMEs through Evaluation and Scoring : Enhancing Food Safety Standards in Kuah Kuwi Noodle MSMEs through Evaluation and Scoring - AR Yelvia Sunarti; Adinda Rizky Prasetya; Cinta Ananda Gustika; Latifa Chusnul Primadhani; Erwan Adi Saputro (Magister Ilmu Lingkungan, Fakultas Teknik dan Sains, UPN Veteran Jawa Timur., 2025)
This study aims to evaluate food safety practices and scoring mechanisms in micro, small, and medium enterprises (MSMEs), with a focus on a noodlebased culinary business, Bakmi Kuah Kuwi. The research adopts a qualitative approach through direct observation and interviews with business owners to examine production activities from raw material procurement to final product presentation. The assessment emphasizes the role of Prerequisite Programs (PRPs) as the foundational support for implementing the Hazard Analysis and Critical Control Points (HACCP) system. Results show that the majority of hazards can be controlled effectively through PRPs and Operational Prerequisite Programs (OPRPs), including sanitation, temperature regulation, and supplier management. However, several Critical Control Points (CCPs) were identified—specifically in the noodle boiling, gyoza steaming, and cooling stages—which require strict monitoring due to their high biological risk. The findings underscore the importance of structured food safety practices in MSMEs and recommend continuous improvement through formal documentation, regular training, and systematic hazard control to ensure product quality and consumer protection.